Diversity studies of freshwater goby species from three rivers ecosystem in Luwuk Banggai, Central Sulawesi, Indonesia. Issue 1 (March 2021) - Gani, A; Adam, M I; Bakri, A A; Adriany, D T; Herjayanto, Muh.; Nurjirana; Mangitung, S F; Andriyono, S
Abstract: Inland public water areas which include freshwater lakes and several rivers in Sulawesi Island have native and endemic fish species which potential as ornamental fish. One of them is a member of Gobiidae. Several studies have reported the species of freshwater goby in Central Sulawesi Province. However, the information is still lacking, especially in the Luwuk Banggai, Central Sulawesi. Therefore, research is needed to examine the diversity of gobies in this area. Observations were conducted in three rivers (Salodik, Kintom, and Simpong). The results of fish inventory in the three Luwuk Banggai rivers obtained 131 fish specimens, namely 26 specimens from the Salodik river, 29 specimens from the Kintom river, and 76 specimens from the Simpong river. The Simpong River has the highest Shannon-Wiener index (H') followed by the Kintom and Salodik rivers, which are 2.6313, 2.0114, and 1.3656, respectively. Similarity analysis of the three rivers produced 2 clusters. The Salodik River in fish diversity shows differences with the other two rivers, while the Simpong and Kintom rivers are in one cluster. Further research is needed related to the biodiversity of gobies and their relationship to habitat characteristics and river water quality in the Luwuk Banggai.